História do passado da conceitualização tradicional à reconfiguração em Walter Benjamin, Martin Heidegger e Sigmund Freud - Augusto Bruno de Carvalho Dias Leite (2017)
The concept of past remains obscure. This thesis aims to discover the history of the concept of past by the presentation of the ontological tradition about the idea of time through a study of three questions posed by ontology: the theological, the physical and the psychic. From this examination, the traditional ontological concept of past can be organized. This concept of past will undergo a theoretical twist at the beginning of the twentieth century by three decisive contributions from the following German thinkers: Walter Benjamin, Martin Heidegger and Sigmund Freud. These three authors have the common goal of breaking with the history of philosophy, reopening the idea of time and the concept of past. This triad structures the concept of past no longer according to the questions proposed by the ontological tradition, but develops a question of its own, namely the questioning of the idea of time from the understanding of its (al)chemical content, in other words, by the understanding of the inherent transience of the modi of temporality and the consequent natural transubstantiation of the forms of time. In this way, the past and other modulations of time become existential forces, no longer places of time (which was the case for the ontological tradition). The theoretical twist that Benjamin, Heidegger and Freud operate results in a new idea of time and a new concept of past whose historiological implications are demonstrated and analyzed through the new terminology about the past. This thesis, therefore, defends that the (al)chemical nature of the concept of past was undercovered by the ontological tradition, only to be discovered by the theoretical twist that affirms the past as an existential force